Comparing and contrasting the behaviour of Arctic and Antarctic sea ice over the 35 year period 1979-2013. Issue 69 (2015) - Simmonds, Ian
Abstract: We examine the evolution of sea-ice extent (SIE) over both polar regions for 35 years from November 1978 to December 2013, as well as for the global total ice (Arctic plus Antarctic). Our examination confirms the ongoing loss of Arctic sea ice, and we find significant ( p ˂ 0.001) negative trends in all months, seasons and in the annual mean. The greatest rate of decrease occurs in September, and corresponds to a loss of 3 x 10 6 km 2 over 35 years. The Antarctic shows positive trends in all seasons and for the annual mean ( p ˂0.01), with summer attaining a reduced significance ( p ˂0.10). Based on our longer record (which includes the remarkable year 2013) the positive Antarctic ice trends can no longer be considered 'small', and the positive trend in the annual mean of (15.29 ± 3.85) x 10 3 km 2 a– 1 is almost one-third of the magnitude of the Arctic annual mean decrease. The global annual mean SIE series exhibits a trend of (–35.29 ± 5.75) x 10 3 km 2 a -1 (p<0.01). Finally we offer some thoughts as to why the SIE trends in the Coupled Model Intercomparison Phase 5 (CMIP5) simulations differ from the observed Antarctic increases.